Strategies for Resilient Build Back in The Post-Flood Era: An AHP-Dematel Technique - Tahir, Muhammad; Idris, Mohd Fadzil Bin Mohd (UI Scholars Hub, 2024)
Pakistan suffered from devastating floods in 2022, causing extensive infrastructural, economic, social, and other damages. Effective risk management was notably absent in the country. Therefore, this paper identifies critical factors influencing the build-back-better (BBB) framework and resilience building. The evaluation of various strategies for risk reduction in infrastructure during floods, ensuring its resilience, is also addressed. This study employs Multi-Criteria Decision Making (MCDM) techniques, specifically the Analytic Hierarchy Process (AHP) and the Decision-Making Trial and Evaluation Laboratory (DEMATEL), to assess critical factors in BBB in the context of devastating floods. The AHP analysis effectively ranked the identified factors based on their relative weights, while DEMATEL determined the inter-relationships among the parameters, categorizing them into effect and cause groups. The results indicate that improvement in structural design is essential, whereas asset replacement is the least important factor. According to the DEMATEL analysis, Cash-for-Work was the most important causal factor in improving resilience-building procedures. The findings of this study assist policymakers in formulating a risk-resilient framework for enhancing construction strategies and developing a strong and resilient infrastructure, effectively influencing associated stakeholders.